Health issues in building services. (Chartered Institution of Building Services Engineers, 2006)
The increasing importance of health issues for building services engineers needs to be emphasised and therefore the decision was taken to include more information on health aspects of building services in CIBSE Guide A: Environmental design. A review of the current legislation was undertaken, along with a review of current guidelines and their relevance to building services engineers. The results of this study are now published as CIBSE TM40: Health issues in building services, and extracts from this publication comprise chapter 8 in the 2006 edition of CIBSE Guide A. The full text of TM40 is also included on the CD-ROM that accompanies CIBSE Guide A. The objective is to inform and educate building service designers and managers of the health implications of the services for which they are responsible, and to give recommendations for limiting, or preferably avoiding, any adverse health effects. --